(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يعدّ هذا العمل استمراراً لدراسة الخصائص الوميضية للبلورات الأحادية. أجري قياس هذه الخصائص: الطيف، زمن الاضمحلال والمردود الطاقي للبلورات CaMoO4 , SrMoO4 الأحادية تحت تأثير أو تهييج الأشعة السينية. أبدت البلورة CaMoO4 مردوداً جيداً (η=20%) مقارنة مع مردود البلورة القياسية ، وزمنَ اضمحلال رئيسي (τ=16μs) بطيئاً. أما البلورة SrMoO4 فأبدت مردوداً (η=6%) وزمن اضمحلال (τ=1μs). أظهرت البلورتان المدروستان لدى تعريضهما للأشعة السينية مقاومة عالية ضد التأثر بهذه الأشعة. أجريت القياسات في جامعة بطرس بورغ التكنولوجية الحكومية- روسيا الاتحادية عام 2006. This work is a continuation to the study of the scintillation characteristics of single crystals. The measurement of these characteristics: spectra, decay time and energy efficiency (yield) for the single CaMoO4, SrMoO4 crystals was effectuated under X-ray excitation. The CaMoO4 crystal has a good energy efficiency (η=20%) comparing to standard crystal, and a slow main decay time (τ=16μs). But the SrMoO4 crystal exhibited (η=6%) efficiency, and (τ=1μs) decay time. the crystals we examined showed high resistance against X-ray radiation. The measurements were done in Tech-Governmental University of Petersburg- Russia, in year 2006.